1982
DOI: 10.1111/j.1365-2222.1982.tb02538.x
|View full text |Cite
|
Sign up to set email alerts
|

Japanese summer‐type hypersensitivity pneumonitis: studies using Cryptococcus antigen

Abstract: Sixty-six patients, diagnosed as Japanese summer-type hypersensitivity pneumonitis at Osaka Prefectural Habikino hospital between 1973 and 1980, were studied. The diagnosis was based on the clinical features and summer-seasonal nature of the disease. The presence of an aetiological agent within patients" home environment was suggested by the recurrence of acute symptoms of high fever, cough and dyspnoea 5-8 hr after coming home from hospital, and by spontaneous improvement on leaving home, immunological studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…One is that this species is often found in the air as first reported by Saito in 1922 (32). The other is that whether this species would be one of the causative agents of Japanese summertype hypersensitivity pneumonitis firstly reported by Miyagawa et al (29), because Shimazu et al reported that one of the causative agents of the disease is Trichosporon cutaneum (33), and also we found that there was serologic cross-reactivity among C. neoformans A, C. albidus (21) and T. cutaneum.…”
Section: R Ikei)asupporting
confidence: 57%
“…One is that this species is often found in the air as first reported by Saito in 1922 (32). The other is that whether this species would be one of the causative agents of Japanese summertype hypersensitivity pneumonitis firstly reported by Miyagawa et al (29), because Shimazu et al reported that one of the causative agents of the disease is Trichosporon cutaneum (33), and also we found that there was serologic cross-reactivity among C. neoformans A, C. albidus (21) and T. cutaneum.…”
Section: R Ikei)asupporting
confidence: 57%
“…The actual extent of subclinical exposure is unknown because an adequate skin test antigen has not been developed for population surveys. However, limited serological studies indicate that most healthy individuals possess antibodies to C. neoformans (23,231,323).…”
Section: Ecology Sexual Reproduction and Identificationmentioning
confidence: 99%
“…They identified T cutaneum as the agent by isolation from the environment of SHP patients. The disease was originally described by Miyagawa et al (11). They reported that SHP patients' sera contained an antibody which reacted with the Cryptococcus species.…”
mentioning
confidence: 99%